Constructing The Working Model of A 2-Up System Pyramid Scheme - Neo, Jia Jie; Lim, Zhen Chung; Teoh, Tze Ying; Muhamad Rasidi, Abdul Rahman; Md Yusof, Zahayu; Misiran, Masnita (Penerbit UMT, 2023)
A pyramid scheme is a business model that is illegal in many countries. It works by recruiting members via promises of payments or services by enrolling more people in the scheme. In recent years, pyramid schemes have been expanding, and many people have fallen victim when the schemes collapse. In this study, the working model and formulation of the 2-up system pyramid scheme are studied to identify its fundamental elements and working mechanism. A model is constructed mathematically to visualise the system’s profitability. To further prove that a pyramid scheme is unsustainable, the limitations of a 2-up system may lead to the collapse of the pyramid structure, and a simulation study on the probability of an individual losing money in a 2-up system is investigated. The method of investigation involved literature reviews and data visualisation. As no references are available on the 2-up system formula, the reading of research articles and websites became the primary source of study. Data visualisation is carried out to showcase the cash flow of profits in a 2-up system pyramid scheme. The fundamental element of the system is for one member to recruit at least three others to prevent a loss as profits from the first two recruits will be channelled to an upline member. According to the investigation of limitations, approximately 65.78% of the world population would need to join the 2-up system when the level rises to 21, where the pyramid structure is vulnerable to collapse. There is a possibility of pyramid scheme members suffering losses since there is a requirement to make a profit. Pyramid schemes are destined to fail in the long run as the possible returns of an individual is never guaranteed